The Relationship Between The Length And Weight of Puput Fish (Ilisha Elongata) Landed at Tanjung Tiram Fishery Port - Erwin Swanto Sapeai; Ria Retno Dewi Sartika Manik; Debora Exaudi Sirait (Jurnal Pendidikan, Sains Sosial, dan Agama, 2020)
Puput Fish (Ilisha Elongata) is an economic fish that is continuously utilized by fisheries actors to meet the demand for public consumption. Research on the Relationship between the Length and Weight of Puput Fish (Ilisha Elongata) Landed at Tanjung Tiram Batu Bara Port was conducted on August 5-September 4, 2025. This study aims to measure the length and weight of Puput Fish (Ilisha Elongata), To determine the body shape of Puput Fish (Ilisha Elongata), To determine the condition of the waters where Puput Fish (Ilisha Elongata) are caught, and the results of this study may be a reference in maintaining Puput Fish (Ilisha Elongata) resources for fishermen who catch Puput Fish (Ilisha Elongata) excessively using survey and analysis methods. The results of this study were obtained from a total of 50 fish, namely fish lengths ranging from 141 mm to 189 mm, where the dominant total length of fish caught was in the average range of 162.08 mm. Meanwhile, the weight of Puput Fish (Ilisha Elongata) ranges from 24 to 52 grams, with an average fish weight of 38.10 grams. The result of the b value calculation obtained in the Puput Fish (Ilisha Elongata) test is 1.3537. Based on the b value obtained, it can be stated that the length of the fish weight is <3, which means negative allometric which means that the length growth is faster than the weight growth. The result of the K calculation in the Puput Fish (Ilisha Elongata) test is 2.7609 which means that the shape of the fish is flat (plump).